2013
DOI: 10.1007/s12072-013-9485-5
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside analogs prevent disease progression in HBV-related acute-on-chronic liver failure: validation of the TPPM model

Abstract: Treatment with nucleoside analogs including entecavir, lamivudine and telbivudine prevented disease progression and increased the survival of patients with HBV-ACLF. Validation of the established TPPM scoring system in this study confirmed its superior predictive value for HBV-ACLF patients when compared with the MELD system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…The recently established and evaluated TPPM model in HBV ACLF patients from a single center large cohort, which displayed a superior predictive ability when compared with MELD and MELD-Na models [n-153]. TPPMs used TBIL, INR, HBV DNA and complications as parameters [153,154]. Based on current multinational cohort, TPPMs demonstrated superiority to CLIF-C OFs, CLIF-C ACLFs, MELDs and MELD-Na in predicting 28-day and 90-day mortality in cirrhotic HBV-ACLF patients [155].…”
Section: Organ Dysfunction and Organ Failure In Aclf For Early Risk Smentioning
confidence: 99%
See 1 more Smart Citation
“…The recently established and evaluated TPPM model in HBV ACLF patients from a single center large cohort, which displayed a superior predictive ability when compared with MELD and MELD-Na models [n-153]. TPPMs used TBIL, INR, HBV DNA and complications as parameters [153,154]. Based on current multinational cohort, TPPMs demonstrated superiority to CLIF-C OFs, CLIF-C ACLFs, MELDs and MELD-Na in predicting 28-day and 90-day mortality in cirrhotic HBV-ACLF patients [155].…”
Section: Organ Dysfunction and Organ Failure In Aclf For Early Risk Smentioning
confidence: 99%
“…The presence of high HBV DNA [> 10(5) copies/ml/ or > 2 × 10 (4) IU/ml] is highly sensitive and specific for the diagnosis [152]. Early and rapid reduction of HBV DNA is the essence of therapy [153]. Several studies have indicated that if the reduction in DNA of > 2 logs could be achieved within 2 weeks, the survival could be improved.…”
Section: Antiviral Strategies In Aclf Hbv Reactivationmentioning
confidence: 99%
“…During follow-up, all patients received nucleotide/nucleoside analogue antiviral treatment with entecavir, telbivudine, lamivudine, or lamivudine combined with adefovir dipivoxil, which could prevent disease progression and would not affect the short-term prognosis for patients in the current study. [7,8] All patients were followed up for 3 months or longer to assess the 3-month mortality.…”
Section: Methodsmentioning
confidence: 99%
“…In Europe, the accuracy of the chronic liver failure-sequential organ failure assessment (CLIF-SOFA) score has been validated, as has the MELD score, for predicting short-term mortality in cirrhotics with acute decompensation [12]. Recently, a TPPM scoring system established by Ning's group with reference to and based on MELD, taking complications, number of organ failures and HBV viral load into consideration, was confirmed to have superior predictive value for HBV-ACLF patients when compared with MELD, and it was further validated in another HBV-ACLF cohort [24,31]. The TPPM scoring system was established based on a population of 531 HBV-ACLF patients from Tongji Hospital (Wuhan).…”
Section: Predictive Models For Organ Failures In Aclfmentioning
confidence: 99%
“…Recent studies demonstrated that treatment with nucleoside analogs including entecavir, lamivudine and telbivudine prevented disease progression and increased the survival of patients with HBV-ACLF [24,31]. Data also showed that the shortterm mortality could be reduced if HBV DNA decreases more than 2 logs within 2 weeks [36,37].…”
Section: Antiviral Treatment For Hbv-related Aclfmentioning
confidence: 99%